The reciprocal relationship between music and visual art: the interplay between melodies and colors – the overall artwork (The International Journal of Educational Sciences and Arts, 2026)
This study examines the structural relationship between music and visual art as two epistemological systems intersecting within the field of aesthetics and reflecting the cognitive structure of human perception. The research departs from the premise that the parallel between auditory rhythm and visual form is not merely formal similarity but rather an expression of multimodal perception and synesthesia, where sensory modalities converge through cognitive and aesthetic synthesis.The study aims to analyze how rhythm in music transforms into visual composition, and how concepts such as time, movement, and space manifest within painting and sculpture as they do within melody and harmony. It also investigates the role of aesthetic awareness in shaping artistic experience by exploring the interplay between form and content across both domains, revealing the unity of perception that underlies sound and image.A descriptive-analytical methodology is employed, integrating the phenomenological approach with structural analysis to connect symbolic systems in auditory and visual arts. The research concludes that aesthetic experience can only be understood as a cognitive construction that transcends disciplinary boundaries, positioning art and music as interdependent epistemic systems through which humanity redefines its relationship with the world by means of synesthetic perception and creative cognition. phenomenological approach with structural analysis to connect symbolic systems in auditory and visual arts. The research concludes that aesthetic experience can only be understood as a cognitive construction that transcends disciplinary boundaries, positioning art and music as interdependent epistemic systems through which humanity redefines its relationship with the world.
Keywords: Aesthetics; Cognitive Structure; Multimodal Perception; Synesthesia; Artistic Rhythm; Aesthetic Awareness; Aesthetic Experience